(untitled) - Stine, R. L. (Milwaukee, 1997)
Baffled at the series of strange, unexplained events taking place at summer camp in the desert wilderness, twelve-year-old Billy considers escaping the horrors forever.
Keywords: Camps; Fiction; Horror stories